2021
DOI: 10.1016/j.mbplus.2021.100066
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold-free 3D cell culture of primary skin fibroblasts induces profound changes of the matrisome

Abstract: The human skin has a highly developed extracellular matrix (ECM) that is vital for proper skin functioning, its 3D architecture playing a pivotal role in support and guidance of resident and invading cells. To establish relevant in vitro models mimicking the complex design observed in vivo, scaffold-based and scaffold-free 3D cell culture systems have been developed. Here we show that scaffold-free systems are well suited for the analysis of ECM protein regulation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…As it has been shown that 3D cell culture better recapitulates in-vivo observations and as 3D cell culture has a profound effect on the composition of the proteome [ 42 , 43 ], additional new insights can be generated by the use of 3D cell culture systems. To better understand potential mechanisms of action, separate 3D cell cultures might still be the method of choice.…”
Section: Discussionmentioning
confidence: 99%
“…As it has been shown that 3D cell culture better recapitulates in-vivo observations and as 3D cell culture has a profound effect on the composition of the proteome [ 42 , 43 ], additional new insights can be generated by the use of 3D cell culture systems. To better understand potential mechanisms of action, separate 3D cell cultures might still be the method of choice.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were concentrated with a SpeedVac vacuum concentrator (Thermo Fisher Scientific), and the final volume was adjusted to 20 μL using buffer A*/A (30% buffer A* with 3% acetonitrile and 0.3% TFA in water, and 70% buffer A). Samples were analysed on a Q Exactive Plus mass spectrometer, coupled to an EasyLC 1000 (Thermo Fisher Scientific), as described [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have been devised to culture 3D cell spheroids of ASCs ( Di Stefano et al, 2020 ; Hoefner et al, 2020 ; Sung et al, 2020 ; Yin et al, 2020 ). In these studies, ULA-3D culture has been more widely used, and in addition to its simplicity and inexpensive nature, this method has the following advantages: it is compatible with many cell lines, initiates by self-assembly, and consists of natural cells and their deposited extracellular matrix (ECM) ( Vu et al, 2021 ). These methods are also more suitable for biological analysis methods that solve basic scientific issues, such as the regulation of protein abundance due to changes in the 3D environment.…”
Section: Introductionmentioning
confidence: 99%